2021
DOI: 10.3389/fphar.2020.581049
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract of Salvia miltiorrhiza Bunge-Radix Puerariae Herb Pair Attenuates Osteoporosis in Ovariectomized Rats Through Suppressing Osteoclast Differentiation

Abstract: Traditional herb pair Salvia miltiorrhiza Bunge-Radix Puerariae (DG) owns various biological activities including anti-inflammatory and anti-oxidative stress. Oxidative stress is one high-risk factor for osteoporosis, then effect of DG on osteoporosis and underlying mechanisms was explored both in vivo and in vitro. Firstly, the predication from network pharmacology hinted that DG has the potential for ameliorating osteoporosis. Consistent with predication, DG significantly restored bone loss and deficiency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 37 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…Increasing evidence displays that autophagy dysregulation results in alteration of osteoclast function and increased bone loss [ 10 ]. Under oxidative stress, autophagy is activated [ 11 ] and accompanied by an unusual increase in osteoclast differentiation and bone resorption [ 12 ]. Thus, the interplay between oxidative stress and autophagy plays a crucial role in cellular homeostasis and the survival of osteoclast.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence displays that autophagy dysregulation results in alteration of osteoclast function and increased bone loss [ 10 ]. Under oxidative stress, autophagy is activated [ 11 ] and accompanied by an unusual increase in osteoclast differentiation and bone resorption [ 12 ]. Thus, the interplay between oxidative stress and autophagy plays a crucial role in cellular homeostasis and the survival of osteoclast.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional Chinese medicine s, Salvia miltiorrhiza Bge and Salvia przewalskii Maxim have been widely used to treat osteoporosis and other related diseases in the clinic. Other active ingredients have also been demonstrated to inhibit osteoporosis by blocking osteoclast production or promoting osteoblast growth ( Guo et al, 2014 ; He et al, 2019 ; Ekeuku et al, 2021 ; Qin et al, 2021 ; Qu et al, 2021 ). DHT, a diterpenoid quinone found in the traditional Chinese medicines, Salvia miltiorrhiza Bge and Salvia przewalskii Maxim , has been widely used to prevent liver injury by modifying the MAPK and NF-κB signaling pathways, reducing neuroinflammatory responses, and inhibiting platelet aggregation.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis (OP) is a metabolic and systemic skeletal disease characterized by increased bone resorption and reduced bone mineral density, which results in increased bone fragility and fracture risk. 1,2 It seriously affects the health and quality of life of the elderly due to its high incidence and disability rate. 3 OP has become a public health issue of universal concern with the inevitable ageing of population.…”
Section: Introductionmentioning
confidence: 99%
“…6 Many studies have reported that excessive bone resorption is the key point of OP, and osteoclast is considered to be the most important target for treating OP. 1,7,8 Currently, the drugs for preventing and curing OP mainly include anabolic agents, anti-catabolic agents, and supplements, such as vitamin K2, calcium, and strontium. 9 However, these drugs have disadvantages such as serious adverse effects and poor efficacy.…”
Section: Introductionmentioning
confidence: 99%